HIPER SEX SEBAGAI DASAR PEMBERIAN IZIN POLIGAMI: Studi Putusan Pengadilan Agama Kabupaten Jember Nomor 1775/Pdt.G/2023/PA Jr - Ash Shiddiqi, Hasbi; El Amin, Faris (Jurnal Indragiri Penelitian Multidisiplin, 2024)
This study aims to analyze hypersexuality as the basis for granting polygamy permits in the decision of the Jember Regency Religious Court No. 1775/Pdt.G/2023/PA Jr. and understand the legal and social implications of the decision in the context of Islamic law in Indonesia. The research method uses a qualitative approach with case studies, collecting data through analysis of verdict documents, interviews with related parties, and literature reviews on polygamy law in Islam and the medical condition of hypersexuality. The results of the study showed that the court recognized hypersexuality as a legitimate medical condition for granting a polygamy permit, taking into account medical evidence and expert testimony and ensuring the conditions of justice for all wives. This decision shows the flexibility of Islamic law in responding to sexual health issues while still paying attention to the principle of justice. The implications of this decision are significant in the practice of Islamic law in Indonesia, could set a precedent for similar cases in the future, and demand strict scrutiny to avoid abuse. Socially, this decision sparked a discussion about the balance between individual needs and justice for all parties in polygamous marriages.